Meta‐analysis of expression of l(3)mbt tumor‐associated germline genes supports the model that a soma‐to‐germline transition is a hallmark of human cancers. Issue 10 (15th November 2013) - Feichtinger, Julia; Larcombe, Lee; McFarlane, Ramsay J.
<x xml:space="preserve">Abstract</x> Evidence is starting to emerge indicating that tumorigenesis in metazoans involves a soma‐to‐germline transition, which may contribute to the acquisition of neoplastic characteristics. Here, we have meta‐analyzed gene expression profiles of the human orthologs of Drosophila melanogaster germline genes that are ectopically expressed in l(3)mbt brain tumors using gene expression datasets derived from a large cohort of human tumors. We find these germline genes, some of which drive oncogenesis in D. melanogaster, are similarly ectopically activated in a wide range of human cancers. Some of these genes normally have expression restricted to the germline, making them of particular clinical interest. Importantly, these analyses provide additional support to the emerging model that proposes a soma‐to‐germline transition is a general hallmark of a wide range of human tumors. This has implications for our understanding of human oncogenesis and the development of new therapeutic and biomarker targets with clinical potential.